The Role of Emotional Skills (Competence) and Coping Strategies in Adolescent Depression - Dario Vucenovic; Gabriela Sipek; Katarina Jelic (MDPI AG, 2023)
Depression is a state of low mood that can lead to several negative outcomes on thoughts, emotions, behaviors, and even physical state. With that in mind, it is important to detect individuals at risk of developing depressive symptoms early and identify protective factors. During the COVID-19 pandemic, adolescents emerged as one of the most vulnerable groups, with deteriorated anxiety and depression due to imposed social isolation, reduced social activities, and concerns over household status, health, and peer support. Distance learning through public service broadcasts and online tools lasted for several months, posing the need for adjustment. This study aimed to assess emotional competence and coping styles as predictors of depression in a sample of adolescents. The study was conducted in-person on a sample of 142 high school students. A high percentage of participants reported above-average levels of depression (21.1% severely depressed). On average, girls reported higher levels of depression than boys (t = 3.86, p < 0.01). Gender differences were also found in emotion-focused coping and avoidance, with girls scoring higher on both (p < 0.05). However, there were no gender differences in problem-focused coping or emotional competence. Hierarchical regression analysis concluded that perceiving and understanding emotions, expressing and naming emotions, regulating emotions, and avoidance were significant predictors of depression. This regression model explained 53% of depression variance, with the regulation of emotions being the most powerful predictor (p < 0.01). No mediating effect of coping styles on the relationship between emotional competence and depression was found in this study.